Implementation of Character Values to Improve Student Resilience in Facing the Society 5.0 Era - Mufidah Auliyah; Sitti Jamilah Amin; Ahdar Ahdar; Muhammad Saleh; Marhani Marhani (Papanda Publisher, 2026)
The Society 5.0 era poses significant challenges to character education in Indonesian Islamic secondary schools (madrasah), where digital disruption threatens to widen the gap between institutional moral objectives and students' actual behaviour. This study investigates the implementation of character values — religiosity, discipline, honesty, creativity, and responsibility — among students at MAN 2 Soppeng, South Sulawesi. Employing a qualitative phenomenological design, data were collected through in-depth interviews with the principal, teachers, and 30 Grade XI students, complemented by observation and documentation. Analysis followed the Miles and Huberman interactive model, with validity ensured through triangulation and member checks. Findings reveal that while character education is systematically delivered through habituation, role modelling, and extracurricular activities, internalisation remains uneven: student compliance is predominantly externally driven rather than grounded in autonomous moral awareness, with the most pronounced gaps in discipline and honesty. Theoretically, these results affirm the integrative relevance of Thomas Lickona's moral knowing–feeling–action framework and Vygotsky's social constructivism, demonstrating that sustainable character formation requires affectively rich, scaffolded, and dialogic pedagogical conditions. These findings contribute an integrative theoretical model applicable to madrasah character education in the Society 5.0 era.